An assessment of factors influencing consumption patterns of sun-dried vegetables among households in Teso South Sub-County, Kenya - Itaru, Annet Regina; Waswa, L.; Jordan, Irmgard; Glas, M.G.; Situma, J.; Shikuri, R. (African Scholarly Science Communications Trust, 2024)
Micronutrient deficiencies are a public health concern affecting more than two billion people worldwide. When adequately consumed, vegetables avert the risk of micronutrient deficiencies. However, low intake of vegetables is common during the dry season due to scarcity and increased prices. This study, a follow-up to the EATSANE project in Teso South sub-county, aimed to assess factors influencing the consumption patterns of sun-dried vegetables among households in Teso South sub-county. The EaTSANE project used the Trials for Improved Practices (TIPs) approach to promote sun drying and consumption of sun-dried vegetables in the study area. This cross-sectional study involved collecting quantitative and qualitative data through interviews and focus group discussions. It targeted women from the TIPs (50) and non-TIPs households (50) of the EaTSANE project. The questionnaire respondent rate was 99% as only 49 women from the TIPs households could be found. The mean ages were 36.82±11.56 and 34.94±10.94 years for the TIPs and non-TIPs participants, respectively. Most TIPs (61.2%) and non-TIPs (56%) participants did not attain primary education and practiced crop farming. Consumption of sun-dried vegetables was reported by the TIPs participants (38.3%) only. The most preferred sun-dried vegetables were cowpea leaves, amaranth, nightshade, pumpkin leaves, jute mallow, and sun hemp, mostly consumed monthly (7.2%). Awareness of the sun-drying technology created by the EaTSANE’s TIPs activities influenced the consumption of sun-dried vegetables [X2 (4) = 35.233, p = .009]. There was no significant relationship between the consumption of sun-dried vegetables and the duration of sun-drying (p > 0.05). However, a chi-square test of independence showed that there was a significant relationship between consumption of sun-dried vegetables and confidence in preparing a meal using sundried vegetables X2 (4, N=99) = 26.964, p = .000). A binary logistic regression analysis further showed that both the ease of preparing sun-dried vegetables (p = 0.006) and the confidence in preparing a meal comprising sun-dried vegetables (p =0.001) were significant (X2 (2) = 34.9, p < 0.001). Sensory attributes including the color (X2 (4, N=99) = 19.3, p = .001) and taste (X2 (4, N=99) = 25.4, p = .000) of sundried vegetables were also significant in influencing their consumption. For improved consumption of sun-dried vegetables, there is a need to create more awareness of the sun-drying technology, especially among households that did not participate in EatSANE’s TIPs activities.